ANALISIS SWOT PENGEMBANGAN PRODUK GRIYA TAKE OVER PADA BANK SYARIAH MANDIRI - Azizah Maulidiah; Rafika Rahmawati (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
PT. Bank Syariah Mandiri Bekasi Area Office one of its products is Griya Take Over which aims to develop Griya product financing. This research was conducted to analyze the strategy to increase the financing of the take over home products at PT. Bank Syariah Mandiri Bekasi Area Office. The analysis used to increase the financing of the take over home by conducting internal and external analysis to develop a strategy using SWOT. This type of research uses descriptive qualitative research with data collection techniques using observation, interviews and documentation. The results of the research on increasing Griya Take Over products are in quadrant I, namely the SO quadrant. From the calculation of the combination strategy, it was found that the highest value was the SO combination with an acquisition value of 4.826, which consisted of introducing the advantages of Griya Take Over products, building a strong brand image in the minds of the people by utilizing events. and exhibition events and make advertisements and brochures as well as print or electronic media.